2005
DOI: 10.1115/1.2033900
|View full text |Cite
|
Sign up to set email alerts
|

Transient and Steady State Vibration Analysis of a Wavy Thrust Bearing

Abstract: This paper describes a numerical procedure for analyzing the dynamics of transient and steady state vibrations in a wavy thrust bearing. The major effects of the wavy geometry and the operating parameters on the dynamic characteristics of the bearing had been discussed in a previous paper; the present paper thus concentrates on examining the relationships between the development of the transient and steady state vibrations when operating conditions are parametrically varied. Special attention is given to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Rasheed 9 found that the bearing load capacity rises at any waviness number in any direction with an increase in wave amplitude. Zhao et al 10,11 examined the stability of a thrust bearing having waviness and reported the enhancement of dynamic characteristics and stability. Wang et al 12,13 reported that the bearing dynamic behaviour and the dynamic characteristics rise as wave amplitude increases.…”
Section: Introductionmentioning
confidence: 99%
“…Rasheed 9 found that the bearing load capacity rises at any waviness number in any direction with an increase in wave amplitude. Zhao et al 10,11 examined the stability of a thrust bearing having waviness and reported the enhancement of dynamic characteristics and stability. Wang et al 12,13 reported that the bearing dynamic behaviour and the dynamic characteristics rise as wave amplitude increases.…”
Section: Introductionmentioning
confidence: 99%